A CASE OF PRENATAL DIAGNOSIS OF INIOENCEPHALY - Полина Евгеньевна Салтыкова; Светлана Владимировна Шрамко; Ирина Анатольевна Сазонова; Елена Михайловна Панкратова (The Publishing House Medicine and Enlightenment, 2022)
A case report of prenatal diagnosis of inioencephaly in a fetus at 19 weeks of gestation is presented. During two consecutive ultrasound examinations, multiple echographic markers were identified: an occipital bone defect, rachischisis of all parts of the spine with a complete absence of cervical and thoracic vertebrae, shortening of the spine, a fixed tilted position of the fetal head («face looking at the sky»), oligohydramnios. By decision of the council and taking into account the desire of the family, the pregnancy was terminated at 21-22 weeks. According to the results of pathological anatomical examination, the diagnosis was confirmed.